Study guides

☆☆

Q: Factor the expression 6x2 plus 11g-35?

Write your answer...

Submit

Still have questions?

Related questions

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

6x2 + 10x = 2x(3x + 5)

6x2=12 2x-28=?

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)

It is the same as: 3y24x+y26x2 that is if y2 and 6x2 means y2 and 6x2 respectively

2x(3x + 5)

6x2+x-35 = (2x+5)(3x-7)

6x2 + 7x - 5 = (3x + 5)(2x - 1)

6x2-18x+12 = (6x-6)(x-2)

It depends if you are adding or subtracting 24y^2. No matter what, factor out 6

First take out the common factor (4):4(6x2 + 2x + 1)6x2 + 2x + 1 cannot be factored, so 4(6x2 + 2x + 1) is as far as you can get with factoring.

Simplifying 6x2 + 23x + 7 Reorder the terms: 7 + 23x + 6x2 Factor a trinomial. (7 + 2x)(1 + 3x) Final result: (7 + 2x)(1 + 3x)

People also asked